Quality of Nursing Care Based on Analysis of Nursing Performance and Nurse and Patient Satisfaction - Abdul Muhith; Nursalam Nursalam (Universitas Airlangga, 2012)
Introduction: Nurses who frequently often contact to patients and most of their time serve patients in 24 hours, have an important role in caring for the patient. Patient satisfaction as quality indicator is the key success for competitiveness of service in hospital. The aim of this research was to develop nursing service quality model based on the nursing performance, nurse and patient satisfaction.Methods: The research method used cross sectional study, at 14 wards of Gresik Hospital. Research factors were namely: oganization characteristic (organization culture and leadership), work factors (feedback and variety of nurses work), nurse characteristics (motivation, attitude, commitment and mental model), nursing practice, interpersonal communication, nurse and patient satisfaction. Statistical analysis of study data was analyzed by Partial Least Square (PLS).Results: The results of nursing performance revealed that nurse characteristic were not affected by organization culture and leadership style, nurse characteristics were affected by work factors, nurse characteristics affected nursing quality service (nursing practice, nursing professional, nurse and patient satisfaction), nurse satisfaction did not affect nursing professionals.Conclusion: Based on the overall results of the development of nursing care model that was originally only emphasizes the process of nursing care only, should be consider the input factor of organizational characteristics, job characteristics, and characteristics of individual nurses and consider the process factors of nursing care standards and professional performance of nurses and to consider the outcome factors nurse and patient satisfaction. So in general the development model of quality of existing nursing care refers to a comprehensive system of quality.